Curriculum development and online instruction for the 21st century - Fudge, Tamara Phillips, 1957-; Ferebee, Susan Shepherd, 1948- (Hershey, PA : Information Science Reference, 2021)
'This book examines the issues surrounding online curriculum and teaching, especially during the current pandemic, and will examine potential solutions and best practices to consider as educators and students move forward with the changes'--
Includes bibliographical references and index.
Keywords: Curriculum planning; Computer-assisted instruction